(untitled) (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2022)
This community service activity is carried out with the aim of increasing product awareness and increasing sales by utilizing the development of digitalization technology. This community service is carried out using a qualitative descriptive method with data collection methods in the form of surveys and observations. The community service activities include preparation and implementation of activities with program outputs including education about NIB, education and implementation of digital marketing and product re-branding to support sales and increase customer awareness.